PERANCANGAN APLIKASI ABSENSI KARYAWAN DENGAN MENGGUNAKAN QR CODE BERBASIS ANDROID - Chen, Dennis; Ekawati, Nia (LPPM Universitas Putera Batam, 2021)
Employees are one of the most important assets for a company. With the satisfaction of employees for the company, it is possible for employees to provide the best for the company. Attendance is an important role in every work agency. Where attendance is one of the main supports that can support and motivate every work activity carried out in it. currently running an attendance system using manual attendance, namely using manual paper. This can result in several mistakes from both the shop and the employee, such as ineffectiveness due to using paper, forgetting the contents of the absence, not being recorded at the time of reporting in one month, or missing paper used. It can also cause carelessness for employees because of the risk of being absent when using manual attendance (paper) which causes manipulation of absent data. By using a QR Code, employees only need to print a QR code using a Smartphone or use a company device that employees can scan using a QR code. In this study, the method used is the waterfall method using Unified Modeling Language (UML) modeling. Then this application is designed with the help of tools from Android Studio and MySQL. This application was built with the aim of making it easier for store owners in attendance for their employees. Keywords: Employees, Attendance, QR Code, UML, Waterfall